2011
DOI: 10.3109/14992027.2010.551220
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and its risk factors in the Beaver Dam Offspring Study

Abstract: OBJECTIVE-To assess the prevalence of tinnitus along with factors potentially associated with having tinnitus. DESIGN-Datawere from the Beaver Dam Offspring Study, an epidemiological cohort study of aging.STUDY SAMPLE-After a personal interview and audiometric examination, participants (n=3267, ages 21-84 years) were classified as having tinnitus if in the past year they reported having tinnitus of at least moderate severity or that caused difficulty in falling asleep.RESULTS-The prevalence of tinnitus was 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
194
6
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(242 citation statements)
references
References 20 publications
17
194
6
14
Order By: Relevance
“…7 The table shows known risk factors for developing tinnitus and associated conditions. The main risk factor is hearing loss, 9 but this association is not simple or straightforward; 3 some people with troublesome tinnitus have audiometrically normal hearing and, conversely, many people with hearing loss do not report tinnitus. People who report high levels of both occupational and recreational noise exposure are more likely to have tinnitus.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…7 The table shows known risk factors for developing tinnitus and associated conditions. The main risk factor is hearing loss, 9 but this association is not simple or straightforward; 3 some people with troublesome tinnitus have audiometrically normal hearing and, conversely, many people with hearing loss do not report tinnitus. People who report high levels of both occupational and recreational noise exposure are more likely to have tinnitus.…”
Section: Epidemiologymentioning
confidence: 99%
“…People who report high levels of both occupational and recreational noise exposure are more likely to have tinnitus. 9 Other factors such as obesity, smoking, alcohol…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing loss has been established as a major risk factor for tinnitus (Nondahl et al 2011). It has been suggested that degraded auditory input due to cochlear damage can trigger aberrant neuronal activity that is interpreted as tinnitus (Preece et al 2003;Eggermont & Roberts 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is approximately 10% 2 which means that it affects many in a population. There are a number of factors that are known to increase the risk of developing tinnitus such as hearing loss, exposure to noise, mood disorders, facial muscular tensions, especially dysfunction of the temporomandibular joint and many drugs including salicylates and some antibiotics 3,4 . The pathophysiological mechanism behind tinnitus has been broadly discussed and still remains unclear even if it is widely recognized as of central (CNS), not peripheral, auditory system origin.…”
Section: Introductionmentioning
confidence: 99%